Heat-not-burn tobacco (HnBT): Isu Pengganti Produk Rokok dan Dampak Kesehatannya: Analisis - Agustiawan Agustiawan (PT Kalbe Farma Tbk., 2025)
The health risks caused by cigarette smoking have led companies to develop and advertise alternative nicotine products, such as e-cigarettes and “heat-not-burn” (HnB) without burning tobacco. United States Federal Drug Administration (US FDA) approved the product I Quit Ordinary Smoking (IQOS) for commercial purposes in the United States. HnB tobacco products heats tobacco (up to 350°C) to produce nicotine aerosol that is inhaled without burning it at a much higher temperature (800°C). Reports show that 37% HnB users experienced at least one symptom, the most was sore throat (25.1%) followed by eye discomfort (22.3%). The notion that HnB tobacco product is an alternative to reduce the impact of conventional cigarettes is not entirely true. HnB tobacco can still have negative health impacts.